WHEN TREATMENT BACKFIRES: SEVERE HYPOTONIC HYPONATREMIA INDUCED BY ANGIOTENSIN RECEPTOR BLOCKERS - Husain, Najihah; Borhan, Marisa Khatijah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Angiotensin receptor blockers (ARBs) are commonly used antihypertensive medications. ARBs may cause worsening of renal function and hyperkalemia, necessitating renal profile monitoring after their initiation. We report a case of severe hypotonic hyponatremia in an elderly patient who was started on valsartan. CASE A 70-year-old Malay female with underlying hypertension was recently prescribed valsartan 80 mg OD by her primary care (PC) doctor for blood pressure optimization. Notably, she had a history of adrenal insufficiency secondary to exogenous steroid use but had successfully discontinued oral hydrocortisone after an adequate Synacthen test response 2 years ago. Four days after starting valsartan, she presented to the Emergency Department (ED) with dizziness and vomiting. Laboratory results revealed severe hypotonic hyponatremia (serum sodium 110 mmol/L, serum osmolality 259 mOsm/kg, urine osmolality 247 mOsm/kg, urine Na 71 mmol/L) and hyperkalemia (serum potassium 7.0 mmol/L). In the ED, she was given a lytic cocktail and 150 cc of 3% saline. Prior to starting valsartan, her serum sodium at the PC clinic was 135 mmol/L. She denied using any over-the-counter or traditional medications. Her blood pressure and blood glucose levels were normal throughout hospitalization, making adrenal insufficiency less likely. Further investigations, including morning serum cortisol (500.4 nmol/L) and TSH (0.54 mIU/L, NR 0.4–4.0 mIU/L), were normal. Thus, the diagnosis of severe hypotonic hyponatremia secondary to valsartan was made. After withholding valsartan, her symptoms resolved, the serum sodium and potassium normalized, and she was discharged well 4 days later. CONCLUSION ARBs can lead to severe hyponatremia by blocking the angiotensin II receptor, which inhibits renal tubular sodium reabsorption. This effect is particularly pronounced in the elderly and individuals on concomitant thiazide therapy. Although rare, ARB-associated hyponatremia should be considered in patients with hypotonic hyponatremia when other causes have been ruled out.